The Influence of Mindful Parenting on Parenting Stress of Housewives in Accompanying Middle Childhood Age Children - Safira Sekar Putri, Azzahra; Hutabarat, Amadea; Vania Trixie, Intan; Sovitriana, Rilla (Lafadz Jaya Publisher, 2025)
Raising school-aged children is one of the challenging tasks for mothers, so if a mother is unable to cope with these challenges, she is vulnerable to experiencing parenting stress. This is also felt by housewives in SD X Cianjur City who accompanied their children aged 6-8 years old. In addition to having to accompany children to optimally study, because this age is a stage of transition from learning by playing to a more academic learning period, mothers also have regular domestic tasks that have to be done. These tasks cause mothers to be careless and prone to stress. The purpose of this study is to obtain empirical data on the causality of mindful parenting on parenting stress in distance learning. This study had 78 participants, and the measuring instrument used to measure mindful parenting was Mindfulness in Parenting Scale (MIPQ) with 0.937 reliability. As for measuring parenting stress, the researchers used the Parental Stress Scale (PSS) with 0.965 reliability. The researcher used a simple linear regression test statistical technique with a regression coefficient of -.628 and a determination coefficient of 68.2%. These results show that if the mother has low mindful parenting behavior, it will cause high parenting stress.